Synthesis, Antinociceptive, Antiinflammatory and AntiepilepticEvaluation of Some Novel Indeno[1, 2-b] Quinoxalin-11-ylidenamines: Novel indeno quinoxalin - Aiyalu Rajasekaran, (Iranian Journal of Pharmaceutical Sciences, 2007)
A series of novel indeno[1, 2-b]quinoxalin-11-ylidenamines 2-9 have been synthesized via condensation of indane[1, 2-b]quinoxalin-11-one (1) with various primary aromatic amines in presence of AcOH for 3 h. Compound 1 was synthesized by condensation of indane-1,2,3-trione with benzene-1,2-diamine in presence of AcOH. The synthesized compounds were characterized by IR, 1H-NMR, mass pectra and elemental analysis. Compounds 2-9 were screened for anti-nociceptive, anti-inflammatory and antiepileptic activity by AcOH induced writhing method ,carrageenan induced paw edema method and maximal electroshock induced convulsion method respectively. Out of the eight synthesized compounds, indeno[1,2-b]quinoxalin-11-ylidine (4-nitrophenyl)amine (3) exhibited promising anti-inflammatory activity and anti-nociceptive activity. N-(2,4-dinitrophenyl)-N'-(indeno[1,2-b]quinoxalin-11-ylidene)hydrazine (7) showed promising anti-inflammatory activity, anti-nociceptive activity, and antiepileptic activity, whereas N4-indeno[1, 2-b]quinoxalin-11-ylidene biphenyl-4,4'-diamine (8) showed promising anti-inflammatory activity.